Results of an international drug testing service for cryptomarket users - Caudevilla, F.; Ventura, M.; Fornís, I.; Barratt, Monica; Vidal, C.; lladanosa, C.; Quintana, P.; Muñoz, A.; Calzada, N. (Elsevier BV, 2015)
Introduction: User surveys indicate that expectations of higher drug purity are a key reason for cryptomarket use. In 2014-2015, Spain's NGO Energy Control conducted a 1-year pilot project to provide a testing service to cryptomarket drug users using the Transnational European Drug Information (TEDI) guidelines. In this paper, we present content and purity data from the trial. Methods: 219 samples were analyzed by gas chromatography associated with mass spectrometry (GC/MS). Users were asked to report what substance they allegedly purchased. Results: 40 different advertised substances were reported, although 77.6% were common recreational drugs (cocaine, MDMA, amphetamines, LSD, ketamine, cannabis). In 200 samples (91.3%), the main result of analysis matched the advertised substance. Where the advertised compound was detected, purity levels (m. ±. SD) were: cocaine 71.6. ±. 19.4%; MDMA (crystal) 88.3. ±. 1.4%; MDMA (pills) 133.3. ±. 38.4. mg; Amphetamine (speed) 51.3. ±. 33.9%; LSD 123.6. ±. 40.5. µg; Cannabis resin THC: 16.5. ±. 7.5% CBD: 3.4. ±. 1.5%; Ketamine 71.3. ±. 38.4%. 39.8% of cocaine samples contained the adulterant levamisole (11.6. ±. 8%). No adulterants were found in MDMA and LSD samples. Discussion: The largest collection of test results from drug samples delivered from cryptomarkets are reported in this study. Most substances contained the advertised ingredient and most samples were of high purity. The representativeness of these results is unknown.